Recent Publications (Quarterly Journal of Economics, 1939)
Recent Publications Get access The Quarterly Journal of Economics, Volume 53, Issue 4, August 1939, Pages 651–655, https://doi.org/10.1093/qje/53.4.651 Published: 01 August 1939